Surveillance of pathogenic yeasts in hospital environments in Taiwan in 2020 - De-Jiun Tsai; Li-Yun Hsieh; Pei-Jung Chung; Yin-Zhi Chen; Yi-Jyun Jhou; Kuo-Yun Tseng; Chia-Jui Yang; Yen-Cheng Yeh; Seng-Yi Lin; Susan Shin-Jung Lee; Ting-I Wu; Tsung-Ta Chiang; et al. (Journal of Microbiology, Immunology and Infection)
Background: A predominate azole-resistant Candida tropicalis clade 4 genotype causing candidemia has been detected in not only Taiwan but also China, Singapore, and Australia. It can also be detected on fruit surfaces. In addition to determining distribution and drug susceptibilities of pathogenic yeasts in environments of intensive care units of 25 hospitals in Taiwan, we would also like to investigate whether the azole-resistant C. tropicalis exists in Taiwan's hospital environment. Methods: The swabs of hospital environments were collected from August to November in 2020 and were cultured for yeasts. The yeasts were identified by rDNA sequence and the antifungal susceptibilities of those isolates were determined by the broth microdilution method. Results: The average yeast-culture rate of hospitals was 9.4% (217/2299). Sinks had the highest yeast-positive culture rate (32.7%), followed by bedside tables (28.9%), floors (26.0%), water-dispenser buttons (23.8%), and TV controller/touch panels (19.0%). Of 262 identified isolates, Candida parapsilosis was the most common species, accounting for 22.1%, followed by Filobasidium uniguttulatum (18.3%), Candida albicans (9.5%), C. tropicalis (8.0%), Candida glabrata (Nakaseomyces glabratus) (6.9%), and 30 other species (35.1%). Of the 21 C. tropicalis isolates from 11 units in 9 hospitals, 15 diploid sequence types (DSTs) were identified. The two DST506 fluconazole-resistant ones belonged to clade 4. Conclusion: We detected not only various pathogenic yeast species but also the predominant clade 4 genotype of azole-resistant C. tropicalis. Our findings highlight and re-emphasize the importance of regular cleaning and disinfection practices.